Morphological characteristics of eskers in areas with soft and hard bed: Examples from Poland and Finland - Frydrych, Małgorzata; Ahokangas, Elina; Mäkinen, Joni; Lejzerowicz, Anna (Elsevier Ltd, 2026)
Constraining esker characteristics is crucial for understanding subglacial processes and reconstructing past ice sheet behaviour. This study compares the morphological characteristics of eskers in areas with soft and hard beds, using examples from Poland and Finland. Eskers in both regions display similar elongation, average sinuosity, and orientation, suggesting control by similar ice-stream configurations affecting the hydraulic gradient towards the ice margin. Differences arise in the lengths, widths, heights, fragmentation, and spacing of eskers, influenced by the lithology and transmissivity of the substratum. In soft bed areas, eskers are less fragmented and show a more stable and gradual ice stream retreat, often associated with tunnel valleys and controlled by subglacial porewater pressure and groundwater flow patterns. Hard bed areas exhibit eskers influenced by bedrock topography, with more reorganization of ice flow and meltwater drainage. The study highlights the impact of substrate properties on esker distribution and morphology, emphasizing the significance of subglacial hydrology and depositional environments in esker formation.